2021
DOI: 10.3171/2019.9.jns191202
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral pallidotomy in the treatment of cervical dystonia: a retrospective observational study

Abstract: OBJECTIVEThe objective of this study was to assess the efficacy of unilateral pallidotomy in patients with asymmetrical cervical dystonia.METHODSThis study retrospectively included 25 consecutive patients with asymmetrical cervical dystonia refractory to botulinum toxin injections, who underwent unilateral pallidotomy between January 2015 and April 2017. Toronto Western Spasmodic Torticollis Rating Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 36 publications
(68 reference statements)
1
24
0
Order By: Relevance
“…There have been few reports of unilateral pallidotomy for dystonia 17,26,27,31,32 . Ondo et al reported that unilateral pallidotomy led to a 50%–73.9% improvement in the BFMDRS score of two and one patients with trauma‐induced and hereditary dystonia respectively 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been few reports of unilateral pallidotomy for dystonia 17,26,27,31,32 . Ondo et al reported that unilateral pallidotomy led to a 50%–73.9% improvement in the BFMDRS score of two and one patients with trauma‐induced and hereditary dystonia respectively 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information regarding the pallidotomy procedure has been described in previous articles. 17…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Dystonia in the craniocervical region including blepharospasm, tongue protrusion dystonia, or cervical dystonia usually require bilateral surgical interventions. However, previous studies reported on some patients with craniocervical dystonia who responded successfully to unilateral surgical intervention [ 15 16 17 18 19 ]. Bilateral ablative procedures are associated with risks of possible complications including dysarthria, dysphagia, and dysphonia.…”
Section: Discussionmentioning
confidence: 99%
“…For detailed information about the pallidotomy and pallidothalamic tractotomy procedures, please refer to our previous reports. 8,9 Patient 2…”
Section: Patientmentioning
confidence: 99%
“…At the 2‐year follow‐up, his dystonic symptoms were stable and no significant postoperative complications were found. For detailed information about the pallidotomy and pallidothalamic tractotomy procedures, please refer to our previous reports 8,9 …”
Section: Case Reportsmentioning
confidence: 99%